Comparison of two multiaxial fatigue models applied to dental implants (Fracture and Structural Integrity, 2015)
This paper presents two multiaxial fatigue life prediction models applied to a commercial dental implant. One model is called Variable Initiation Length Model and takes into account both the crack initiation and propagation phases. The second model combines the Theory of Critical Distance with a critical plane damage model to characterise the initiation and initial propagation of micro/meso cracks in the material. This paper discusses which material properties are necessary for the implementation of these models and how to obtain them in the laboratory from simple test specimens. It also describes the FE models developed for the stress/strain and stress intensity factor characterisation in the implant. The results of applying both life prediction models are compared with experimental results arising from the application of ISO-14801 standard to a commercial dental implant
Keywords: Dental implants